Integration of Web-based and PC-based Clinical Research Databases - Brandt, C. A.; Sun, K.; Charpentier, P.; Nadkarni, P. M. (Methods of Information in Medicine, 2004)
We have created a Web-based repository or data library of information about measurement instruments used in studies of multi-factorial geriatric health conditions (the Geriatrics Research Instrument Library – GRIL) based upon existing features of two separate clinical study data management systems. GRIL allows browsing, searching, and selecting measurement instruments based upon criteria such as keywords and areas of applicability. Measurement instruments selected can be printed and/or included in an automatically generated standalone microcomputer database application, which can be downloaded by investigators for use in data collection and data management.Methods: Integration of database applications requires the creation of a common semantic model, and mapping from each system to this model. Various database schema conflicts at the table and attribute level must be identified and resolved prior to integration. Using a conflict taxonomy and a mapping schema facilitates this process.Results: Critical conflicts at the table level that required resolution included name and relationship differences.Conclusions: A major benefit of integration efforts is the sharing of features and cross-fertilization of applications created for similar purposes in different operating environments. Integration of applications mandates some degree of metadata model unification.
Keywords: Database interoperation; clinical research database management systems